Effect of Ag and Cu doping on the properties of ZnO magnetron sputtered thin films for biomedical applications - Milisav, Ana Marija; Mičetić, Maja; Dubček, Pavo; Sotelo, Lamborghini; Cantallops-Vilà, Cristina; Erceg, Ina; Fontanot, Tommaso; Bojanić, Krunoslav; Fiket, Željka; Ivanić, Maja; Sarau, George; Christiansen, Silke; et al. (Applied Surface Science, 2025)
Hospital-acquired infections are a major challenge for the healthcare system. The development of antibacterial surfaces for medical devices and non-critical surfaces in healthcare facilities is gaining attention as a promising strategy to prevent them. In this study, the properties of biodegradable magnetron-sputtered ZnO thin films doped with Ag and Cu were compared. In addition, biomimetic deposition of calcium phosphates (CaPs) on these surfaces was explored. The investigated thin films doped were prepared by co-deposition in a multi-source magnetron sputtering system. X-ray diffraction of the prepared thin films revealed the formation of wurtzite in all cases. Grazing incidence small-angle X-ray scattering showed the formation of nanoparticles whose lateral-to-vertical diameter decreased with increasing Ag content and increased with increasing Cu content. The opposite influence of increasing Ag and Cu content in the thin films on grain size and water contact angle were also observed. The biomimetic deposition of calcium phosphates (CaP) resulted in partial coverage of the surface of all thin films investigated with apatitic phase. CaP deposition resulted in a reduced WCA as well as a slightly reduced release of Cu and an increased release of Ag ions, while the release of Zn remained unaffected. Even though the tested surfaces exhibited cytotoxicity, CaP deposition enhanced MG-63 cell viability, especially for Ag-doped ZnO thin films, and improved the prevention of S. aureus and P. aeruginosa biofilm formation. The results confirmed the potential of magnetron sputtering to coat materials for biomedical antibacterial applications and pointed to a viable strategy for preparing biocompatible surfaces.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Antibacterial coating; Biofilm; Calcium phosphate; Cytotoxicity; Magnetron sputtering

Optimization of titanium and titanium alloy surface properties by ultra-short laser processing for improved antibacterial characteristics - Aceti, D. M.; Daskalova, A.; Angelova, L.; Filipov, E.; Sotelo, Lamborghini; Andreeva, A.; Trifonov, A.; Buchvarov, I. (Journal of Physics: Conference Series, 2022)
The aim of the current study is to improve in a one step process the properties of Ti and Ti alloy surfaces by enhancing their bioactivity in order to provide better conditions for microbial rejection. We propose to alter the biomaterial characteristics by a method alternative to the chemical ones, namely, non-contact processing of the surface by ultra-short laser pulses. The laser-induced modification results in a surface with different topographic features and an increased presence of oxides. We performed hierarchical laser patterning of the surface inducing the formation of areas covered by nanostructures, or laser-induced periodic surface structures (LIPSS), alternating with areas covered by micropillars in their turn surmounted by LIPSS. The increased roughness achieved due to the presence of micropillars, together with a marked presence of oxides, has been proven by several studies to enhance the biocompatibility of the material by improving the surface wettability and, furthermore, promoting the cells adhesion and osseointegration, while reducing the adhesion of pathogens. The laser processed surface, consisting of a pattern of parallel lines, showed improved and anisotropic wettability. The water contact angle value decreased by â1/410° in a direction orthogonal to the lines of the pattern, and by â1/440° in a parallel direction.
CRIS-Team Scopus Importer:2022-05-20

Poly(Amino Acid) LbL Multilayers With Embedded Silver and Copper Oxide Nanoparticles as Biocompatible Antibacterial Coatings - Milisav, Ana Marija; Sotelo, Lamborghini; Cantallops-Vilà, Cristina; Fontanot, Tommaso; Erceg, Ina; Bojanić, Krunoslav; Vuletić, Tomislav; Fiket, Željka; Ivanić, Maja; Christiansen, Silke; Meurice, Edwige; Dutour Sikirić, Maja (Advanced Materials Interfaces, 2024)
The growing concern over implant-associated infections motivates the development of novel antibacterial coatings for medical devices as an effective strategy in reducing the occurrence of IAI. Polyelectrolyte multilayers (PEMs) incorporating metal/metal oxide nanoparticles (NPs) as antimicrobial components receive special attention for their ability to coat diverse surface types and low potential to induce antimicrobial resistance. This study investigates the potential of poly(amino acid) multilayers consisting of poly-L-lysine and poly-L-glutamic acid with embedded silver (PEMAg) or copper oxide (PEMCuO) deposited on titanium surfaces for the coating of medical surfaces. The results of the quartz crystal microbalance with dissipation, scanning electron microscopy, and electron dispersive spectroscopy show that both types of NPs are successfully incorporated in the PEM and deposited over the entire coated surface. The incorporation of NPs in PEM prevents the burst release. The viability of MG-63 cells is higher than 70% on all investigated PEMs, confirming their biocompatibility. PEMCuO shows better biofilm prevention compared to PEMAg, entirely preventing Pseudomonas aeruginosa biofilm and allowing the formation of only weak Staphylococcus aureus biofilm. The results obtained confirm the high potential of poly(amino acids) multilayers with embedded metal/metal oxide NPs as biocompatible antimicrobial coatings for medical devices.
CRIS-Team Scopus Importer:2025-02-04
Keywords: antibacterial coatings; copper oxide nanoparticles; cytotoxicity; polyelectrolyte multilayers; silver nanoparticles

Single-Step Process for Titanium Surface Micro-and Nano-Structuring and In Situ Silver Nanoparticles Formation by Ultra-Short Laser Patterning - Aceti, Dante Maria; Filipov, Emil; Angelova, Liliya; Sotelo, Lamborghini; Fontanot, Tommaso; Yousefi, Peyman; Christiansen, Silke; Leuchs, Gerd; Stanimirov, Stanislav; Trifonov, Anton; Buchvarov, Ivan; Daskalova, Albena (Materials, 2022)
Ultra-short laser (USL)-induced surface structuring combined with nanoparticles synthesis by multiphoton photoreduction represents a novel single-step approach for commercially pure titanium (cp-Ti) surface enhancement. Such a combination leads to the formation of distinct topographical features covered by nanoparticles. The USL processing of cp-Ti in an aqueous solu-tion of silver nitrate (AgNO3) induces the formation of micron-sized spikes surmounted by silver nanoparticles (AgNPs). The proposed approach combines the structuring and oxidation of the Ti surface and the synthesis of AgNPs in a one-step process, without the use of additional chemicals or a complex apparatus. Such a process is easy to implement, versatile and sustainable compared to alternative methodologies capable of obtaining comparable results. Antimicrobial surfaces on medical devices (e.g., surgical tools or implants), for which titanium is widely used, can be realized due to the simultaneous presence of AgNPs and micro/nano-structured surface topography. The pro-cessed surfaces were examined by means of a scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM) and Raman spectroscopy. The surface morphology and the oxidation, quality and quantity of AgNPs were analyzed in relation to process parameters (laser scanning speed and AgNO3 concentration), as well as the effect of AgNPs on the Raman signal of Titanium oxide.
CRIS-Team Scopus Importer:2022-07-22
Keywords: laser ablation; multiphoton photo-reduction; silver nanoparticles; surface patterning; titanium; ultra-short laser processing

Surface structuring of β-TCP and transition to α-TCP induced by femtosecond laser processing - Aceti, D. M.; Filipov, E.; Sotelo, Lamborghini; Fontanot, T.; Christiansen, S.; Lasgorceix, M.; Leriche, A.; Buchvarov, I.; Daskalova, A. (Journal of Physics: Conference Series, 2023)
Tricalcium phosphate (Ca3(PO4)2, TCP), is one of the most studied and used as material for bioresorbable implants. The β phase has a slower dissolution dynamic and ensures mechanical support for a longer time in biological environment, while a faster release of ions characterize the α phase that trigger a stronger biological response. In this work a femtosecond laser system was used to process β-TCP pellets surface. The femtosecond laser processing results in surface morphology modification, by turning the flat mirror polished surface into a rough and opaque one. The morphological and phisycochemical characteristics of material surface were studied by means of SEM, AFM, Raman, XRD and contact angle measurement. The processed surface showed the formation of micro and nano roughness alongside, furthermore a partial phase transformation from β-TCP to α-TCP was detected. A significant improvement in surface wettability for three different liquids (i.e.water, ethylene glycol and diiodo-methane) is reported. This implies an increase in surface free energy as well. The combination of α and β phase, together with the increased roughness obtained by laser processing, could positively affect the cell adhesion and metabolic activity.
CRIS-Team Scopus Importer:2023-06-02

Ultra-short laser surface properties optimization of biocompatibility characteristics of 3d poly-ε-caprolactone and hydroxyapatite composite scaffolds - Daskalova, Albena; Filipov, Emil; Angelova, Liliya; Stefanov, Radostin; Tatchev, Dragomir; Avdeev, Georgi; Sotelo, Lamborghini; Christiansen, Silke; Sarau, George; Leuchs, Gerd; Iordanova, Ekaterina; Buchvarov, Ivan (Materials, 2021)
The use of laser processing for the creation of diverse morphological patterns onto the surface of polymer scaffolds represents a method for overcoming bacterial biofilm formation and inducing enhanced cellular dynamics. We have investigated the influence of ultra-short laser pa-rameters on 3D-printed poly-ε-caprolactone (PCL) and poly-ε-caprolactone/hydroxyapatite (PCL/HA) scaffolds with the aim of creating submicron geometrical features to improve the matrix biocompatibility properties. Specifically, the present research was focused on monitoring the effect of the laser fluence (F) and the number of applied pulses (N) on the morphological, chemical and mechanical properties of the scaffolds. SEM analysis revealed that the femtosecond laser treatment of the scaffolds led to the formation of two distinct surface geometrical patterns, microchannels and single microprotrusions, without triggering collateral damage to the surrounding zones. We found that the microchannel structures favor the hydrophilicity properties. As demonstrated by the com-puter tomography results, surface roughness of the modified zones increases compared to the non-modified surface, without influencing the mechanical stability of the 3D matrices. The X-ray diffraction analysis confirmed that the laser structuring of the matrices did not lead to a change in the semi-crystalline phase of the PCL. The combinations of two types of geometrical designs—wood pile and snowflake—with laser-induced morphologies in the form of channels and columns are considered for optimizing the conditions for establishing an ideal scaffold, namely, precise dimensional form, mechanical stability, improved cytocompatibility and antibacterial behavior.
CRIS-Team Scopus Importer:2021-12-31
Keywords: Antibacterial structuring; Biodegradable polymers; Bone tissue engineering; Surface patterns; Ultra-short laser processing